Pemberdayaan Perempuan melalui Pelatihan Pembuatan Spray Anti Nyamuk Herbal untuk Meningkatkan Pendapatan Ibu-Ibu di Desa Alai Selatan - Wira Alvio; Ahmad Subarkah; Janisah Janisah; Eka Sugesti; Juwita Maharani; Putri Rizki R; Alya Fadhilla R.; Putri Adelia (Jurnal Pengabdian Masyarakat, 2026)
Women empowerment is an important strategy in improving family economic welfare at the village level. Alai Selatan Village, Muara Enim Regency, has the potential of lemongrass plants that have not been optimally utilized as economic products. This community service program aims to improve the skills of village women in producing herbal mosquito repellent spray made from lemongrass and 90% alcohol as a home-based business opportunity. The implementation method included socialization, hands-on training, mentoring, and evaluation stages. The activity was conducted at the Alai Selatan Village Office and received enthusiastic participation from village women. The results showed an increase in participants’ knowledge and skills in the production process as well as motivation to develop the product as an additional source of family income. This program aligns with the KKN theme “women empowerment in improving family economy” and contributes to strengthening local resource-based economic development and increasing the role of women in family economic empowerment.